Women of Vigorous Spirit: Gender Stereotypes and Roles in the Conquest of America in the 16th Century (2024)
This text investigates how certain exceptional actions carried out by women in the military sphere during the conquest of America in the 16th century were documented, interpreted, and narrated by witnesses and chroniclers. These accounts were influenced by gender archetypes and stereotypes shaped and influenced by the prevailing social, religious, moral and cultural conventions of that period. The article analyzes some paradigmatic cases from the early Peruvian viceroyalty. This analysis is conducted from a gender perspective that enables the examination of aspects such as female models transferred to the New World and the consideration of the actions of some women in frontier territories, where various factors allowed for, and even demanded, roles far removed from the norms of Early Modern society.